Virtual Reality in Education: Educators Perspective of Accepting the Technology based on TAM - M, Raja; Priya G G, Lakshmi (International Journal of Psychosocial Rehabilitation, 2020)
One of the most promising technologies in this fast-changing world is virtual reality. It is expected that virtual reality technologies will become an inevitable part of education and training needs. While the term virtual reality is very commonly used for gaming, it is also evident that this technology has contributed a lot and simplified many tedious learning processes. Education is getting a new dimension with the help of virtual worlds, realistic simulations, and the immersion offered by virtual reality applications. Especially complex and abstract concepts can be explained easily with lesser efforts as well as expenditure, but at the same time, due to its limitations, there are still some mixed opinions on this technology. The readiness of teachers is one of the important factors that contribute to the implementation of this technology in classrooms. This study was carried out with a population of 92 educators from southern India, and the Technology Acceptance Model (TAM) was used as an aid in determining the acceptance level of the participants. The results showed that the ease of use of VR applications, their availability, and awareness of their usage would enhance the intention to use them.